Amyand’s hernia - Nigam, Vinod Kumar; Nigam, Siddharth (International Surgery Journal, 2019)
Amyand’s hernia is the presence of a vermiform appendix in an inguinal hernia sac, the appendix may be normal or inflamed. It is named after Claudius Amyand (1685-1740), who was surgeon at St. George’s Hospital, London, U.K. He removed successfully an inflamed appendix from hernia sac of an eleven year old boy in 1736. Amyand’s hernia is a rare and difficult to diagnose preoperatively. Authors are presenting here a case of Amyand’s hernia in a 78 years old male on right side which was diagnosed on operation. Review of literature on Amyand’s hernia is done with reminder to keep Amyand’s hernia in mind while operating inguinal hernia.